Can paternal preconceptional radiation account for the increase of leukaemia and non-Hodgkin's lymphoma in Seascale? - Kinlen, L (1993)
OBJECTIVE: To determine if the excess of leukaemia and non-Hodgkin's lymphoma in Seascale is restricted to those born in the parish and whether it might be explained by the postulated relation with paternal preconceptional radiation. DESIGN: Comparison, separately for those born in the parish and those born elsewhere, of the numbers of these malignancies observed in Seascale with those expected on the basis of reference rates for England and Wales. Details of paternal radiation levels were sought for each case. SETTING: The parish of Seascale in west Cumbria. SUBJECTS: Residents of Seascale below age 25 years in the years 1951-91. MAIN OUTCOME MEASURES: The observed and expected numbers of cases of leukaemia and non-Hodgkin's lymphoma within Seascale among those born there and among those born elsewhere. Also, the levels of any paternal preconceptional radiation associated with each case. RESULTS: A significant excess of leukaemia and non-Hodgkin's lymphoma at ages 0-24 was found in Seascale in those who were born there (ratio of observed to expected cases 8.6 and 20.2 respectively; p < 0.01). This also applied to those not born there (7.2 and 16.5; p < 0.01), a group often regarded as not showing an excess. The estimates were then conservatively recalculated so as to overestimate the risks among those born in Seascale and underestimate them among those born elsewhere. On this basis the six cases in those born in Seascale compare with 0.38 expected (15.8; p < 0.001), of which two were associated with paternal preconceptional life-time levels of 100 mSv or greater and three others with levels of 90-99 mSv. Among those born elsewhere, there were five cases (expected 0.74; ratio 6.7, p < 0.01), of which only one was associated with a high level of such radiation. CONCLUSIONS: Paternal preconceptional radiation cannot be the sole cause of the excess in Seascale since it will not explain the excess among those born outside Seascale. It follows that, unless two causes are to be postulated, any single cause must be a factor other than paternal preconceptional radiation. On this basis, the association found among those born there, if not partly due to chance, may reflect an indirect relation with the true cause. The recent hypothesis about such paternal radiation has originated in a subgroup of the excess cases that have aroused concern.